Multi-perspective APT Attack Risk Assessment Framework using Risk-Aware Problem Domain Ontology - Park, Sihn Hye; Jung, Ji Wook; Lee, Seok Won (Proceedings of the IEEE International Conference on Requirements Engineering, 2021)
Cyber-attacks, which affect a wide range of areas such as political, economic, and social organizations, continue to evolve along with rapid changes in the IT environment, becoming more intelligent and complex. Especially, APT attacks have specific targets with obvious goals and use complex strategies from multiple perspectives. To proactively defend against these potential attacks, it is important to assess security risks based on a comprehensive and systematic understanding of APT attacks. In this paper, we propose the APT Attack Risk Assessment Framework to evaluate the security risks for specific APT attacks, using Risk-Aware Problem Domain Ontology. The proposed framework can assess the risks in which a specific APT attack affects an organization within a domain.
Keywords: Advanced persistent threat; Domain ontologies; Multi-perspective; Problem domain; Problem domain ontology; Risk assessment framework; Risk aware; Security requirements; Security risk assessments; Security risks; Advanced Persistent Threat; Problem Domain Ontology; Security Requirements; Security Risk Assessment